2021
DOI: 10.12913/22998624/129951
|View full text |Cite
|
Sign up to set email alerts
|

Fractographic Assessment and FEM Energy Analysis of the Penetrability of a 6061-T Aluminum Ballistic Panel by a Fragment Simulating Projectile

Abstract: In aviation and light vehicles, aluminum plates are often used instead of heavy shields as ballistic shields. The standard shrapnel was used in the analysis due to the fact that under hazardous conditions, the shrapnel destruction occurs more often than directly with a bullet. Analyses were performed in which the initial velocity and the angle of impact were the variables. The material of the aluminum plate (ballistic shield) with a thickness of 1 mm was divided into three-dimensional C3D4 tetragonal elements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In order to accelerate the performed calculations, the bullet model was designed as a nondeformable shell object, type Discrete rigid, base feature Shell, with a mesh type R3D4 (a 4-node 3-D bilinear rigid quadrilateral) composed of 700 finite elements. The bullet geometry is inspired by the 9 × 19 mm Parabellum pistol cartridge (Nieoczym & Drozd, 2021).…”
Section: 𝜂 = −𝑝 𝑞mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to accelerate the performed calculations, the bullet model was designed as a nondeformable shell object, type Discrete rigid, base feature Shell, with a mesh type R3D4 (a 4-node 3-D bilinear rigid quadrilateral) composed of 700 finite elements. The bullet geometry is inspired by the 9 × 19 mm Parabellum pistol cartridge (Nieoczym & Drozd, 2021).…”
Section: 𝜂 = −𝑝 𝑞mentioning
confidence: 99%
“…It has also been observed that the most favourable situation is that the structure of the armour plate is not damaged by the projectile, which results in the ballistic protection of the plate not being affected. It should be borne in mind that in certain situations increasing the angle of inclination of the plate is not a fully effective method of protection, due to the possibility of the aforementioned ricochets causing damage to other people or other vehicles (Nieoczym & Drozd, 2021).…”
Section: Introductionmentioning
confidence: 99%